Preharvest and Postharvest Factors in Sustainable Quality Management of Ornamental Plants - Çelikel, F.G. (International Society for Horticultural Science, 2024)
Other than genetics, we know all cultural practices and environmental conditions during production may greatly determine the postharvest quality and longevity of ornamental plants. We are only able to maintain the high quality obtained by proper cultivation under optimum ecology. Unfortunately, we lose a significant part of the produced cut flowers/greens and pot plants after harvest. The lost product has a huge carbon footprint. Care is the most sustainable factor in quality management to prevent postharvest losses since it needs no energy resource. However, the most important postharvest factor in maintaining quality and preventing losses of perishable crops is temperature. At low temperature, not only aging processes and fungal development are greatly suppressed, but also negative gravitropic bending is eliminated. Besides, there is no need storing or transporting the flowers in solution/water at low temperature. Therefore, the living products that are not sensitive to chilling injury should be stored and transported at temperature close to 0°C to keep them fresh from grower to consumer. However, lower temperatures mean more energy to use. Thus, sustainable cooling and transport are needed for sustainability to reduce energy used. Eco-friendly treatments are another important issue in the sustainability of the flower industry. After harvest, cut flowers and pot plants are commonly treated with a range of compounds to prolong the postharvest life. Ecofriendly and sustainable sprays or pulsing and vase solutions such as natural extracts from medicinal plants should be preferred as a biocide in solutions to maintain the postharvest quality of cut flowers/greens and pot plants. Ethylene is a problem for sensitive cut flowers and plants. 1-Methylcyclopropene is an ecofriendly alternative to the commonly used silver thiosulphate. Disease life cycle and triangle as well as microbiome should be considered in postharvest control strategies to avoid using harmful chemicals. Biodegradable recyclable packaging materials and sustainable coatings should be preferred to reduce plastic waste. As conclusion, sustainable quality management of flower chain from grower to consumer not only reduce postharvest losses but also chemicals and energy used and plastic waste during the value chain. © 2024 International Society for Horticultural Science. All rights reserved.
Keywords: Care; Eco-Friendly Treatments; Ethylene; Postharvest Losses; Temperature